INFORMATION SYSTEM FOR SALES OF CAKES USING THE WATERFALL METHOD IN THE RATIH SHOP - Muhammad Naufal Rifqi; Rima Tamara Aldisa (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research is to design and develop an information system for selling cookies at Ratih shop using the Waterfall method. The Waterfall method was chosen because of its systematic and gradual structure, starting from requirements analysis, system design, implementation, testing, to maintenance, enabling efficient and structured system development. Ratih shop, which operates in the field of selling pastries, faces challenges in managing its sales and product inventory. By implementing a specially designed information system, stores are expected to improve operational efficiency, accuracy of sales and inventory data, as well as increase customer satisfaction through faster and more accurate service. This system integrates various sales functions, from ordering, sales, to stock management, and provides reports that help in making strategic decisions. It is hoped that the results of this research can be used as a reference for similar stores that want to improve their business processes through implementing an effective sales information system.